Conditional fractional matching preclusion for burnt pancake graphs and pancake-like graphs. Issue 4 (2nd October 2022) - Gupta, Sambhav; Cheng, Eddie; Lipták, Lászlo
ABSTRACT: The conditional fractional strong matching preclusion number of a graph G is the minimum size of F such that F ⊂ V ( G ) ∪ E ( G ) and G − F has neither a fractional perfect matching nor an isolated vertex. In this paper, we obtain the conditional fractional strong matching preclusion number for burnt pancake graphs and a subset of the class of pancake-like graphs.